An Efficient and Fair Solution for Communication Graph Games - Rene van den Brink; Anna Khmelnitskaya; Gerard van der Laan (Tinbergen Institute, 2011)
We introduce an efficient solution for games with communication graph structures and show that it is characterized by efficiency, fairness and a new axiom called component balancedness. This latter axiom compares for every component in the communication graph the total payoff to the players of this component in the game itself to the total payoff of these players when applying the solution to the subgame induced by this component.
Keywords: C71; 330; TU game; communication graph; Myerson value; fairness; efficiency; Transferable Utility Games; Kooperatives Spiel; Theorie